2020
DOI: 10.1111/jfd.13256
|View full text |Cite
|
Sign up to set email alerts
|

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans

Abstract: Cryptocaryon irritans, a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C. irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…It was interesting to find that all these signalling molecules were up‐regulated in the infected local mucosal sites (skin and gill) at most tested time points. In the same study, with the presence of C. irritans in the skin and gill of E. coioides , upregulated expression of histocompatibility complex II ( MHC II ) was detected 38 . The results mentioned above might suggest that the increased accumulation of IgT + B cells, CD8α + cells and MHC II‐positive cells in the skin and gill of E. coioides after they were infected with C. irritans .…”
Section: Irritans‐induced Histological Changes In Fishmentioning
confidence: 80%
See 1 more Smart Citation
“…It was interesting to find that all these signalling molecules were up‐regulated in the infected local mucosal sites (skin and gill) at most tested time points. In the same study, with the presence of C. irritans in the skin and gill of E. coioides , upregulated expression of histocompatibility complex II ( MHC II ) was detected 38 . The results mentioned above might suggest that the increased accumulation of IgT + B cells, CD8α + cells and MHC II‐positive cells in the skin and gill of E. coioides after they were infected with C. irritans .…”
Section: Irritans‐induced Histological Changes In Fishmentioning
confidence: 80%
“…In the same study, with the presence of C. irritans in the skin and gill of E. coioides, upregulated expression of histocompatibility complex II (MHC II) was detected. 38 The results mentioned above might suggest that the increased accumulation of IgT + B cells, CD8α + cells and MHC II-positive cells in the skin and gill of E. coioides after they were infected with C. irritans. Nevertheless, in view of the fact that upregulated mRNA expression of these genes does not mean that they are also up-regulated at protein level, further functional studies of these proteins may be required.…”
Section: F I G U R Ementioning
confidence: 96%
“…Similarly, a study of the molecular mechanism in the gills of O. mykiss by using transcriptome analysis found that some increased immune-related genes were significantly related with antigen processing and presentation in the infected gills [ 13 ]. Several antigen processing and immune-relevant proteins included major histocompatibility complex (MHC I/II), heat shock proteins (Hsp70/90A/A1) and calreticulin (CALR/3b) were crucial for the host immune defense against bacterial infection [ 9 ]. The MHC molecules may have participated in antigen presentation for specific immunity by modulating mechanism through interactions with T-lymphocyte and Natural killer cells in animals [ 13 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidences indicated that fish gill tissue provides major point of entry for pathogens and attachment sites [ 8 ]. And a great deal of immune-relevant genes participate in the gill local immune response, adding its most important function for immune response and survival in fish [ 6 , 9 , 10 ]. Previous studies demonstrated that several key immune-related genes such as tumor necrosis factor [ 6 ], interleukins [ 11 ] , heat shock proteins [ 12 ], major histocompatibility complex [ 9 ] and complements [ [10] , [13] , [14] ] were identified with respect to the involvement in immune defenses of gills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation